URGENSI KESADARAN BUDAYA KONSELOR DALAM MELAKSANAKAN LAYANAN BIMBINGAN DAN KONSELING UNTUK MENGHADAPI MASYARAKAT EKONOMI ASEAN (MEA) - Gumilang, Galang Surya (Universitas Muhammadiyah Metro, 2015)
Abstract: Humans live in this world depends on culture. Culture greatly affect every aspect of human life that occurred as a whole according to the demands and needs. Human activity ranging from waking to sleep again did not escape the influence of culture. Culture is indeed long life for each event experienced by humans is closely related to culture. For example, as socialize with other people very concerned with culture because every human being has their cultural awareness. Just as a counselor when faced counselee when giving guidance and counseling services. The counselor must have the cultural awareness in the face of the counselee for bringing the essence of each culture. In providing guidance and counseling services, counselors need to pay attention to cultural awareness of being able to bring counselees to understand the psychological characteristics such as intelligence (intelligence, emotional, and spiritual), aptitude, attitude, motivation, and others. Counselors in Indonesia are still not paying attention because of cultural awareness in the provision of guidance and counseling services helped form a new behavior and to determine the success of the counseling process.Keywords: cultural counselor, guidance and counseling services, the ASEAN economic community